Analisis Tingkat Kebisingan Jalan Raya Tanah Baru dan Jalan Raya Bogor - Amelia Indah Indriani; Neng Nenden Mulyaningsih (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
Noise is one of the main environmental health problems in big cities. Noise is unwanted sound that can interfere with and or endanger health. Highway traffic is a major source of disturbing noise for most urban society. The impact of noise in the residential environment on public health includes: physiological disorders, psychological disorders, complaints and communication complaints. That The purpose of this study was to determine the noise level on Jalan Raya Tanah Baru and Jalan Raya Bogor and to find out whether the noise level on Jalan Raya Tanah Baru and Jalan Raya Bogor is still feasible for humans hearing. Based on the research that has been done, it is found that the noise level on Jalan Raya Tanah Baru is 71.5 dB. With the highest average noise level of 76 dB which occurred in the morning 08.30-09.00 WIB while the noise level on Jalan Raya Bogor was 76.16 Db with the highest average noise level of 80 db which occurred in the morning at 08.30-09.00 WIB and in the afternoon at 18.00-18.30 WIB. From the data, it can be seen that the noise level on Jalan Raya Bogor is higher than that on Jalan Raya Tanah Baru. This is caused by the number of vehicles passing on Jalan Raya Bogor more than Jalan Raya Tanah Baru. The noise level on Jalan Raya Tanah Baru and Jalan Raya Bogor is already at the level of "strong" and this is not good for health especially in human hearing.